Financial Management / Theory and Practice: Fourth Edition - Brigham Eugene F; Gapenski Louis C (The Dryden Press, 1985)
Introduction, An Overview of Financial Management, Business Organizations and Financial Statements and Taxes, Financial Markets and Institutions and Interest Rates, Valuation and the Cost of Capital, Time Value of Money, Bond and Stock Valuation Models, Risk and Rates of Return, The Cost of Capital, Capital Budgeting, The Basics of Capital Budgeting, Risk Analysis and the Optimal Capital Budget, Capital Structure and Divident Policy, Capital Structure Theory, Capital Structure Policy, Dividend Policy, Types of Long-Term Capital, Lease Financing, Working Capital Management, Inventory Management, Financial Analysis and Planning, Financial Statement Analysis, Financial Planning and Control, Special Topics in Financial Management, Bankruptcy and Reorganization, Multinational Finance, Pension Plan Management, Appendices, Index.
Introduction, An Overview of Financial Management, Business Organizations and Financial Statements and Taxes, Financial Markets and Institutions and Interest Rates, Valuation and the Cost of Capital, Time Value of Money, Bond and Stock Valuation Models, Risk and Rates of Return, The Cost of Capital, Capital Budgeting, The Basics of Capital Budgeting, Risk Analysis and the Optimal Capital Budget, Capital Structure and Divident Policy, Capital Structure Theory, Capital Structure Policy, Dividend Policy, Types of Long-Term Capital, Lease Financing, Working Capital Management, Inventory Management, Financial Analysis and Planning, Financial Statement Analysis, Financial Planning and Control, Special Topics in Financial Management, Bankruptcy and Reorganization, Multinational Finance, Pension Plan Management, Appendices, Index.